(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2013)
Hybrid electric vehicles (HEV) draw much attention during the last years due to the need for alternative power resources with reduced emissions. The major disadvantages of HEV are the heavy weight, high cost and complicated control strategies. This paper focuses on a developed design for electro-mechanical differential unit. Most designer uses differential block as a mechanical linkage between two power sources. In this paper the differential unit is modified to do more than linkage. It acts as a continuously-varying-transmission (CVT), electric motivation unit and power regeneration unit. This of course leads to more compact and light weight vehicles.The developed model uses three main units: Synchronous block, Differential block, and Induction block the three blocks are combined in a compact design. Mechanical-electrical power transformation is carried out through the synchronous block which acts also as regeneration unit during braking. On the other hand electrical-mechanical transformation is carried out through the induction unit. The differential unit plays the role of smart linkage between the synchronous and the induction units. Simulation through Matlab-simulink is carried to show the validity of the model. The developed model proved to satisfy the properties of CVT and driving demands torques.